Anabolic Steroid Use for Weight and Strength Gain in Critically Ill Patients: A Case Series and Review of the Literature. (7th May 2018) - Anstey, Matthew; Desai, Shilpa; Torre, Luke; Wibrow, Bradley; Seet, Jason; Osnain, Emma
Abstract : Background. An important long-term complication of critical illness is significant weakness and its resulting functional impairment. Recent advances have aimed to prevent critical illness weakness via early mobilisation of patients, minimising sedation, and optimising nutrition. One other potential treatment may be to provide anabolic support in the recovery phase, especially as patients have decreased levels of anabolic hormones. Case Presentation. We describe a case series of 4 patients who had either (1) profound critical illness myopathy and (2) profound weight loss. All patients were already receiving appropriate nutritional support and physiotherapy. All patients had functional improvements in their muscle strength. Conclusions. For patients in the recovery phase of critical illness, we provide examples of when anabolic steroid supplementation may assist the treating clinicians in rehabilitating their patients who are still in the Intensive Care Unit. We discuss patient selection and the current supporting literature for anabolic supplementation in critically ill patients.